Pengaruh Tekanan Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Bank Syariah Indonesia KP Jakarta - Rafaza, Ahmad; Rosmita, Rosmita (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Abstracts - This study aims to analyze the influence of work pressure and work environment on employee performance at PT Bank Syariah Indonesia Head Office in Jakarta. The research is based on the importance of creating optimal working conditions to sustainably improve employee productivity and performance, especially amid the post-pandemic work dynamics and increasing service targets in the banking sector. This study uses an associative quantitative method, with data collected through questionnaires distributed to 106 respondents. The data were analyzed using multiple linear regression with SPSS version 27. The results show that work pressure has a significant negative effect on employee performance, while the work environment has a significant positive effect. Simultaneously, work pressure and work environment significantly influence employee performance, contributing 85.2% to performance variation. These findings indicate that to enhance employee performance effectively, companies must manage work pressure wisely and create a supportive and comfortable work environment. Keywords: Work Pressure, Work Environment, Employee Performance